2017
DOI: 10.1007/s00284-017-1368-x
|View full text |Cite
|
Sign up to set email alerts
|

The Distal Gut Bacterial Community of Some Primates and Carnivora

Abstract: Huge numbers of bacteria reside in the digestive tract of host and these microorganisms play a vital role in the host health, especially in the digestion of food and the development of immune system. Host phylogeny and diet, especially long-term diet, both have great influence on the gut bacterial community. Other aspects of host, such as gender, age, and the geography and weather they lived, are also correlated to their gut bacterial community. Feces are usually used for gut bacteria study and fecal bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…2a ). These findings suggest that host evolutionary history has a stronger effect on total archaeal community diversity among host species relative to diet (both general dietary categories and specific components), which corresponds with existing evidence of an association between archaeal diversity and host phylogeny 12 , 14 . However, these results contrast with our previous Bacteria-biased survey of the same sample data set, in which diet was an equal if not stronger explanatory variable relative to host phylogeny 13 .…”
Section: Discussionsupporting
confidence: 86%
“…2a ). These findings suggest that host evolutionary history has a stronger effect on total archaeal community diversity among host species relative to diet (both general dietary categories and specific components), which corresponds with existing evidence of an association between archaeal diversity and host phylogeny 12 , 14 . However, these results contrast with our previous Bacteria-biased survey of the same sample data set, in which diet was an equal if not stronger explanatory variable relative to host phylogeny 13 .…”
Section: Discussionsupporting
confidence: 86%
“…Both host phylogeny and diet correlated with beta diversity, but host phylogeny was more consistently significant among diversity metrics and showed stronger correlations (Figure 2A). These findings suggest that host evolutionary history has a stronger effect on total archaeal community diversity among host species relative to diet (both general dietary categories and specific components), which corresponds with existing evidence of an association between archaeal diversity and host phylogeny (12, 14). Still, these results contrast our previous Bacteria-biased survey of the same sample dataset, in which diet was an equal if not stronger explanatory variable relative to host phylogeny (13).…”
Section: Discussionsupporting
confidence: 86%
“…While previous work has indicated that host phylogeny influences archaeal abundance (1214, 30, 42), the work has largely been focused on methanogen diversity (especially Methanobrevibacter) and was strongly biased towards mammals. In this work, we not only identified a signal of host-Archaea phylosymbiosis while accounting for host diet, habitat, and other factors (Figure 2A), but we also identified specific archaeal ASVs to be associated with host phylogeny globally and for particular host clades (Figures 2C & S12), and we observed a significant signal of cophylogeny (Figure 2D & 2E).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on bacterial 16S rRNA gene of mitochondrial DNA (mtDNA) as the substitution rate is high, making this locus valuable for distinguishing organisms, especially among closely related species (Hillis & Dixon, 1991;Long & Dawid, 1980;Osorio, Collins, Romalde, & Toranzo, 2005). Further, metagenomic studies using 16S rRNA gene have been widely used to characterize gut microbial communities in wildlife such as bats, primates, tigers, and birds (Carrillo-Araujo et al, 2015;Chen et al, 2018;Garcia-Mazcorro et al, 2017;Philips et al, 2012). It has been shown that two variant regions in 16S rRNA gene, namely V3 and V4, provide sufficient phylogenetic information on bacteria (Huse et al, 2008;Liu, Lozupone, Hamady, Bushman, & Knight, 2007).…”
Section: Introductionmentioning
confidence: 99%